Uremic Pericarditis with Cardiac Tamponade in a Patient on Hemodialysis - Nismat Javed; Marcos Molina; Rabih Nasr; Gilda Diaz-Fuentes (Case Reports in Cardiology)
Uremic pericardial effusion and pericarditis in end-stage kidney disease patients remain one of the causes responsible for high rates of morbidity and occasional mortality. While clinical presentation could be variable, clinicians should have a high index of suspicion for uremic pericarditis especially in patients who miss their dialysis sessions. We present a 77-year-old man with end-stage renal disease on dialysis diagnosed with pericarditis and large pericardial effusion complicated by cardiac tamponade and shock. He underwent urgent pericardiocentesis with clinical improvement. The course of the disease can be complicated by shock with multiorgan failure, particularly the liver. The presentation is relatively acute requiring a high level of suspicion, urgent diagnosis, and management to reduce mortality. As the geriatric population increases with associated comorbid conditions, it would be expected that patients undergoing dialysis would increase. Given the uncommon nature of the disease and how these patients have been managed by multiple specialties and care providers, it is important to consider dialysis-related complications in all patients with end-stage renal disease presenting with dyspnea.